1996
DOI: 10.1046/j.1365-2117.1996.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal history analysis by integrated modelling of apatite fission track and vitrinite reflectance data: application to an inverted basin (Buller Coalfield, New Zealand)

Abstract: Integrated analysis and modelling of apatite fission track with vitrinite reflectance (VR) data allows the timing, magnitude and pattern of Palaeogene subsidence and Neogene inversion to be established for an uplifted and largely denuded basin: the Buller Coalfield, New Zealand. At the time of maximum subsidence in the late Oligocene, the basin consisted of an extensional half graben, bounded to the west by the Kongahu Fault Zone (KFZ), with up to 6 km of upper Eocene to Oligocene section adjacent to it; curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 0 publications
1
27
1
Order By: Relevance
“…Minor conglomerates were deposited adjacent to the proto-Alpine Fault in the upper Grey valley and east Murchison areas, and mudstones and flysch were deposited in the Inangahua-Grey valley trough and areas to the north. Inversion of the Buller coalfield region began c. 24-23 Ma (Kamp et al 1996).…”
Section: Ma (Mid Waitakian)mentioning
confidence: 99%
“…Minor conglomerates were deposited adjacent to the proto-Alpine Fault in the upper Grey valley and east Murchison areas, and mudstones and flysch were deposited in the Inangahua-Grey valley trough and areas to the north. Inversion of the Buller coalfield region began c. 24-23 Ma (Kamp et al 1996).…”
Section: Ma (Mid Waitakian)mentioning
confidence: 99%
“…Subsequent heat flow calculations incorporating new BHT data from the Taranaki and Great South Basins, north and southeast of the West Coast, respectively, have suggested that the conductivities used by Pandey (1981) were too high . Kamp et al (1996) studied in detail the thermostratigraphic history of the Buller Coalfield, an inverted basin northwest of Westport, using integrated vitrinite reflectance and apatite fission track data. However, Kamp et al did not address the transient thermal history of the basin specifically, but instead assumed a constant geothermal gradient and surface temperature for the 40 m.y.…”
Section: G97028 Received 9 May 1997; Accepted 27 August 1998mentioning
confidence: 99%
“…23–20 Ma, is consistent with the change in convergence rates at ca. 20 Ma (Figure b), and has been observed in northwestern South Island, west of the Alpine Fault (Ghisetti et al, ; Kamp, Webster, & Nathan, ; Lihou, ; Nathan et al, ). Despite this contraction, marine facies persisted through many of the basins west of the Alpine Fault during the earliest Miocene, with limited supply of terrigenous sediment to most West Coast basins and the STB at this time (Figure a).…”
Section: Regional Tectonic Implicationsmentioning
confidence: 80%
“…13 and ca. 7 Ma (Reilly et al, ; Figure c), eastern North Island (Field et al, ; Nicol et al, ), the West Coast region (Ghisetti et al, ; Kamp et al, ) and in the hanging‐wall of the Alpine Fault (Tippett & Kamp, ).…”
Section: Regional Tectonic Implicationsmentioning
confidence: 99%